The Importance of Patient Expectations: A Mixed-Methods Study of U.S. Psychiatrists - Rosenfield, Maayan N.; Bernstein, Michael H. (Frontiers in Psychiatry, 2021)
Objective: To examine how psychiatrists think about and modulate nonspecific factors (e.g., hope, expectations) in clinical practice. Methods: U.S. psychiatrists were recruited for two studies assessing attitudes and behaviors related to nonspecific factors. Study 1 entailed remote qualitative focus groups (k=7) with n=26 participants (36.0% female). Study 2 was a quantitative survey with n=346 respondents (34.0% female) designed to assess the generalizability of focus group findings. Results: Four themes were identified in Study 1 that were used to inform the survey (Study 2): 1) Expectations 2) Hope, 3) Placebo Effect, and 4) Aesthetic Features. Nearly all surveyed psychiatrists (92.2%) considered patient expectations at least “most of the time” when interacting with a patient. Focus groups revealed that psychiatrists often attempt to balance optimism and realism to improve outcomes. A majority of survey respondents believe office design and physician attire could at least somewhat influence expectations (72.5% and 77.3%, respectively) and even outcomes (51.5% and 58.7%, respectively). Focus group psychiatrists described how physical features may be used as therapeutic tools. Conclusions: Psychiatrists are highly mindful of patient expectations. Although there is variability in the perceived importance of expectations, hope, the placebo effect, and aesthetic features, many utilize these factors in clinical practice.